Filgotinib (GLPG0634/GS-6034), an oral JAK1 selective inhibitor, is effective in combination with methotrexate (MTX) in patients with active rheumatoid arthritis and insufficient response to MTX: results from a randomised, dose-finding study (DARWIN 1). Issue 6 (19th December 2016) - Westhovens, R; Taylor, P C; Alten, R; Pavlova, D; Enríquez-Sosa, F; Mazur, M; Greenwald, M; Van der Aa, A; Vanhoutte, F; Tasset, C; Harrison, P
Abstract : Objectives: To evaluate the efficacy and safety of different doses and regimens of filgotinib, an oral Janus kinase 1 inhibitor, as add-on treatment to methotrexate (MTX) in patients with active rheumatoid arthritis (RA) and inadequate response to MTX. Methods: In this 24-week phase IIb study, patients with moderate-to-severe active RA receiving a stable dose of MTX were randomised (1:1:1:1:1:1:1) to receive placebo or 50, 100 or 200 mg filgotinib, administered once daily or twice daily. Primary end point was the percentage of patients achieving a week 12 American College of Rheumatology (ACR)20 response. Results: Overall, 594 patients were randomised and treated. At week 12, significantly more patients receiving filgotinib 100 mg once daily or 200 mg daily (both regimens) achieved an ACR20 response versus placebo. For other key end points at week 12 (ACR50, ACR-N, Disease Activity Score based on 28 joints and C reactive protein value, Clinical Disease Activity Index, Simplified Disease Activity Index and Health Assessment Questionnaire-Disability Index), differences in favour of 100  or 200 mg filgotinib daily were seen versus placebo; responses were maintained or improved through to week 24. Rapid onset of action and dose-dependent responses were observed for most efficacy end points and were associated with an increased haemoglobin concentration. No significant differences between once-daily and twice-daily regimens were seen. Treatment-emergent adverse event rates were similar in placebo and filgotinib groups. Serious infections occurred in one and five patients in the placebo and filgotinib groups, respectively. No tuberculosis or opportunistic infections were reported. Conclusions: Filgotinib as add-on to MTX improved the signs and symptoms of active RA over 24 weeks and was associated with a rapid onset of action. Filgotinib was generally well tolerated. Trial registration number: NCT01888874 .